2020
DOI: 10.1097/meg.0000000000001942
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s perspective on the implementation of measures to contain the SARS-CoV-2 pandemic in a Portuguese Gastroenterology Department

Abstract: Figure 1 Sex and age group distribution (%) Figure 2 Working people according to age distribution,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…It proved to be a valuable tool to keep healthcare providers in contact with their patients while avoiding the risk of infection. Recent studies assessing patients' perspectives have reported high acceptability and satisfaction rates for this model [ 16 , 17 ]. However, it might not be appropriate for certain patients and specific situations, which require individual adaptations.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It proved to be a valuable tool to keep healthcare providers in contact with their patients while avoiding the risk of infection. Recent studies assessing patients' perspectives have reported high acceptability and satisfaction rates for this model [ 16 , 17 ]. However, it might not be appropriate for certain patients and specific situations, which require individual adaptations.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…6,12 IBD patients have shown positive attitudes towards receiving ongoing digital care for follow-up consultations. [17][18][19][20][21] IBD patients have also significantly benefited from telecare by having reduced travel time, distances and out-of-pocket costs when accessing follow-up appointments virtually instead of in-person. 3 Landmark telehealth projects, such as Project ECHO, have transformed hepatology practice.…”
Section: Paper Journal and Year Summarymentioning
confidence: 99%
“…In a survey study of 115 individuals with IBD in Italy (of whom 100 completed the questionnaire), trust in telemedicine services for consultation and desire to continue to use telemedicine services was >90% ( 15 ). Additionally, in a Portuguese survey study of 973 individuals with IBD, 88.8% supported remote consultations and 77.3% were satisfied with this type of appointment ( 16 ). Although less commonly reported, some centres even utilized social media and alternate communication platforms (e.g., WeChat) in order to facilitate the delivery of virtual care ( 8 ).…”
Section: Changes In Health Care Deliverymentioning
confidence: 99%